Association of Secondary Hyperparathyroidism with Coronary Artery Disease in Patients on Regular Hemodialysis - Azar BARADARAN (Applied Medical Informatics, 2011)
Objective: To understand the association of parathormone excess due to secondary hyperparathyroidism and hyperphosphatemia with coronary artery disease, a study was designed on a group of stable hemodialysis (HD) patients. Methods: This cross-sectional study was carried out on patients undergoing maintenance HD. Blood samples were collected after overnight fasting for serum calcium, phosphorus, and intact serum parathormone (iPTH). The presence of cardiac chest pain was confirmed through the complaint of heart burn or epigastric pain, retrosternal discomfort and chest compression was confirmed by symmetrical depressed T wave at that time on a 12-lead ECG by means of a 12-channel and also reliving the pain after taking sublingual Trinitroglycerine pearls (TNG). Results: A sample of 36 stable HD patients was investigated. The mean age of patients was 46.5±17 years. The length of the time patients have been on hemodialysis were 32± 36 months (Median = 19 months). About 21% of patients had chest pain. Mean±SD of intact PTH of patients was 434±455 pg/ml (Median = 309 pg/ml). In this study, there was a significant difference of hemodialysis duration (p = 0.009), hemodialysis amount (p = 0.029) and also serum phosphorus (p = 0.013) between patients with and without cardiac chest pain. There was also a significant difference of iPTH (p = 0.026) between male hemodialysis patients with and without cardiac chest pain. Conclusion: Our data supported the importance of better control of serum phosphorus and also treatment of parathormone excess as the responsible factors promoting the coronary artery disease in hemodialysis patients.